EKSISTENSI KEJAHATAN MAGIS DALAM HUKUM PIDANA - Ketut Nihan Pundari; Ketut Tjukup (Kertha Negara : Journal Ilmu Hukum, 2013)
Practices of black magic such as santet, pelet, teluh, voodo, guna-guna, ect are aphenomenon of a magical or metaphysical evil crime. Since its existence is beyond commonsense and non fiction, this crime is very difficult to justify in the magical realm of criminallaw, especially in the subject of evidence. Parties who are the victims obtain justice by lawfinally do vigilantism. Therefore, this paper describes how the existence of black magicpractices in Indonesian criminal law sources such as Kitab Undang-Undang Hukum Pidana(KUHP). So if there is a magical crime, the law will be effective to overcome. In addition,this paper also explains how the opinion of legal experts for handling the problem of evilmagic. The method used in this paper is the normative method refers to the sources of law.